Open cup nests evolved from roofed nests in the early passerines. Issue 1848 (8th February 2017) - Price, J. Jordan; Griffith, Simon C.
Abstract : The architectural diversity of nests in the passerine birds (order Passeriformes) is thought to have played an important role in the adaptive radiation of this group, which now comprises more than half of avian species and occupies nearly all terrestrial ecosystems. Here, we present an extensive survey and ancestral state reconstruction of nest design across the passerines, focusing on early Australian lineages and including members of nearly all passerine families worldwide. Most passerines build open cup-shaped nests, whereas a minority build more elaborate domed structures with roofs. We provide strong evidence that, despite their relative rarity today, domed nests were constructed by the common ancestor of all modern passerines. Open cup nests evolved from enclosed domes at least four times independently during early passerine evolution, at least three of which occurred on the Australian continent, yielding several primarily cup-nesting clades that are now widespread and numerically dominant among passerines. Our results show that the ubiquitous and relatively simple cup-shaped nests of many birds today evolved multiple times convergently, suggesting adaptive benefits over earlier roofed designs.